Physicochemical characterization of drinking water from borehole wells in Ulaanbaatar city, Mongolia - Gerelt-Od, Dashdondog; Enkhjargal, Togtokh; Byambasuren, Zorigt; Dagvasuren, Ganbold (Proceedings of the Mongolian Academy of Sciences, 2021)
Groundwater is the most important natural source for supplying of drinking water around the world, especially in rural areas. The 14th khoroo (sub-district) of Khan-Uul district of Ulaanbaatar is only one khoroos where its inhabitants engage in animal husbandry and agriculture, which play an important role in the district’s economic growth, faces an increasing shortage of groundwater due to population and economic growth in the agriculture sector in the sub-district. In this study, we present the hydro-chemical characteristics and spatial distribution of aquifer using GIS and multivariate statistical approaches. During the sampling periods, a total of 51 groundwater samples were collected from 46 deep wells and 5 shallow wells in the area between October and November 2019. Samples included parameters of anions and cations (Na+, K+, Ca2+, Mg2+, Cl-, SO42-, NO3-, HCO3-) and EC. Data from all the samples were subject to cluster and component analysis. As a result, three clusters were defined and it was established that the dominant groundwater type is HCO3-Ca2+-Na+. The parameter of Mg2+ and Ca2+ were not set in the permissible limits of the second and third clusters. Principal component analysis (PCA) illustrated that the northern part of the study area is greater affected to anthropogenic activities and aquifer mineralogy. Moreover, it found that Ca2+ and Mg2+ correlated with each other, which could be helpful in site specific monitoring of groundwater quality. The results of the study will contribute to management and quality control of the groundwater in the city.